2008
DOI: 10.1161/strokeaha.107.508580
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in Ischemic Stroke Rates and the Efficacy of Warfarin Among Patients With Atrial Fibrillation

Abstract: Background and Purpose-Warfarin reduces stroke risk in studies of predominantly white patients with atrial fibrillation (AF). Whether nonwhites also have lower rates of stroke while treated with warfarin is unclear. Methods-A multiethnic stroke-free cohort hospitalized with nonrheumatic AF was identified in a large health maintenance organization. Stroke risk factors (advanced age, diabetes, hypertension, and heart failure), warfarin use, and anticoagulation intensity were assessed. Crude ischemic stroke rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 42 publications
(40 reference statements)
5
46
0
Order By: Relevance
“…A previous study suggested that in Asian populations the administration of warfarin was more effective as compared with white populations in the setting of stroke prevention. 19 Consistent with that finding, our data demonstrated a significantly reduced MACCE rate in relation to triple antithrombotic therapy in Asians. Cox regression analysis indicated non-administration of warfarin and a baseline CHADS2 score ≥2 were independent predictors of overall MACCE.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study suggested that in Asian populations the administration of warfarin was more effective as compared with white populations in the setting of stroke prevention. 19 Consistent with that finding, our data demonstrated a significantly reduced MACCE rate in relation to triple antithrombotic therapy in Asians. Cox regression analysis indicated non-administration of warfarin and a baseline CHADS2 score ≥2 were independent predictors of overall MACCE.…”
Section: Discussionsupporting
confidence: 91%
“…14 The overall mean TTR in our study (53.7%) is also similar to the 54.5% reported for 8992 individuals with AF from Kaiser Permanente Southern California 19 but lower than the 62.5% reported from Kaiser Permanente Northern California. 20 Differences in the proportion of patients newly starting warfarin, the proportion of patients managed through anticoagulation clinics, and the health status of the AF populations studied may partly account for the disparity.…”
Section: Discussionsupporting
confidence: 77%
“…Bhandari et al reported that African-American patients spent less time in range compared with White-American patients (32.2% vs 42.0%, p < 0.001) [27]. Another study showed that African-Americans spent more time in the sub-therapeutic range (INR < 2) [28]. …”
Section: Discussionmentioning
confidence: 99%